Human carbonic anhydrase-8 AAV8 gene therapy inhibits nerve growth factor signaling producing prolonged analgesia and anti-hyperalgesia in mice. Issue 4 (July 2018) - Zhuang, Gerald; Upadhyay, Udita; Tong, Xiaoying; Kang, Yuan; Erasso, Diana; Fu, Eugene; Sarantopoulos, Konstantinos; Martin, Eden; Wiltshire, Tim; Diatchenko, Luda; Smith, Shad; Maixner, William; et al.
Abstract Carbonic anhydrase-8 (Car8 ; murine gene symbol) is an allosteric inhibitor of inositol trisphosphate receptor-1 (ITPR1), which regulates neuronal intracellular calcium release. We previously reported that wild-type Car8 overexpression corrects the baseline allodynia and hyperalgesia associated with calcium dysregulation in the waddle (wdl ) mouse due to a 19 bp deletion in exon 8 of theCar8 gene. In this report, we provide preliminary evidence that overexpression of the human wild-type ortholog ofCar8 (CA8 WT ), but not the reportedCA8 S100P loss-of-function mutation (CA8 MT ), inhibits nerve growth factor (NGF)-induced phosphorylation of ITPR1, TrkA (NGF high-affinity receptor), and ITPR1-mediated cytoplasmic free calcium release in vitro. In addition, we show that gene transfer using AAV8-V5-CA8WT viral particles via sciatic nerve injection demonstrates retrograde transport to dorsal root ganglia (DRG) producing prolonged V5-CA8WT expression, pITPR1 and pTrkA inhibition, and profound analgesia and anti-hyperalgesia in male C57BL/6J mice. AAV8-V5-CA8WT -mediated overexpression prevented and treated allodynia and hyperalgesia associated with chronic neuropathic pain produced by the spinal nerve ligation (SNL) model. These AAV8-V5-CA8 data provide a proof-of-concept for precision medicine through targeted gene therapy of NGF-responsive somatosensory neurons as a long-acting local analgesic able to prevent and treat chronic neuropathic pain through regulating TrkA signaling, ITPR1 activation, and intracellular free calcium release by ITPR1.